1999
DOI: 10.1055/s-2007-971137
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Arginine or Glycine Supplementation on Gastrointestinal Function, Muscle Injury, Serum Amino Acid Concentrations and Performance During a Marathon Run

Abstract: Gastrointestinal bleeding and increased intestinal permeability have been observed in marathon runners. We sought to determine if L-arginine would be useful for prevention of these complications. Twenty-three runners were randomized to receive L-arginine (A) or glycine (placebo) (G), 10 grams 3 times daily for 14 days prior to the 1997 Houston-Methodist Marathon. Serum, stool hemoccults and lactulose:mannitol permeabilities were obtained at baseline, immediately after completion of the marathon and approximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Specifically, arginine is a precursor to polyamines required for intestinal mucosal growth and repair, and for nitric oxide, a potent vasodilator that may protect intestinal barrier integrity by improving splanchnic perfusion, deterring pathogen invasion, and modulating inflammation (28,54). In support, arginine supplementation has preserved intestinal barrier integrity in various animal stress and intestinal injury models (2), although the effects in humans are less clear (5). Cysteine is an essential component of glutathione, an antioxidant tripeptide critical to maintaining a favorable redox balance in the intestine (10).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, arginine is a precursor to polyamines required for intestinal mucosal growth and repair, and for nitric oxide, a potent vasodilator that may protect intestinal barrier integrity by improving splanchnic perfusion, deterring pathogen invasion, and modulating inflammation (28,54). In support, arginine supplementation has preserved intestinal barrier integrity in various animal stress and intestinal injury models (2), although the effects in humans are less clear (5). Cysteine is an essential component of glutathione, an antioxidant tripeptide critical to maintaining a favorable redox balance in the intestine (10).…”
Section: Discussionmentioning
confidence: 99%
“…Because exercise‐induced disturbances to intestinal integrity and endotoxaemia, especially in the reperfusion period after exercise, which may be mediated by free radicals, anti‐oxidant supplementation may prevent further epithelial damage and ameliorate endotoxaemia . L‐citrulline and L‐arginine are precursors for nitric oxide production, which is a potent vasodilator, potentially enhancing blood flow into the intestinal microvasculature reducing exercise‐induced hypoperfusion and ischaemic . Glutamine and bovine colostrum have been proposed to enhance the expression of heat shock proteins (ie, proteins that protect cellular membrane under period of stress), which may protect the intestinal enterocytes, reduce intestinal permeability, and attenuate the development of local inflammatory pathways .…”
Section: Prevention Strategiesmentioning
confidence: 99%
“…In animals and in some clinical populations, such as congestive heart failure, stable angina, and pulmonary hypertension, L-arginine ingestion has demonstrated positive effects on aerobic exercise performance and maximal aerobic power (VO 2max ; Maxwell et al, 2001;Bednarz et al, 2004;Mizuno et al, 1998;Nagaya et al, 2001;Ceremuzyński et al, 1997); however, in healthy, physically active or trained males, the research has shown either a positive effect (Bailey et al, 2010;Schaefer et al, 2002), no effect (Bescós et al, 2009;McConell et al, 2006;Sunderland et al, 2011), or a detrimental effect www.IJSNEM-Journal.com ORIGINAL RESEARCH (Buchman et al, 1999) on performance. Thus there is much controversy as to whether L-arginine supplementation can benefit aerobic endurance performance.…”
Section: The Acute Effects Of L-arginine On Hormonal and Metabolic Rementioning
confidence: 99%